Rapid transformation in aquatic food value chains in three Nigerian states - Liverpool-Tasie, Lenis Saweda O.; Wineman, Ayala; Amadi, Mark Umunna; Gona, Ayuba; Emenekwe, Chukwuemeka Chinonso; Fang, Ming; Olunuga, Olawale; Onyeneke, Robert Ugochukwu; Norbert, Sunday; Adenike, Taiwo Mayomi; Reardon, Thomas; Belton, Ben (Frontiers in Aquaculture, 2024)
Introduction Nigeria is Africa’s most populous country, third largest fish producer, and second largest aquaculture producer. There have been numerous studies of aquaculture and fisheries in Nigeria, but no study to date has analyzed aquaculture and capture fisheries value chains together, while giving equal weight to all value chain segments and systematically capturing information on temporal trends in value chain structure, conduct, and performance. This paper does so. Methods We conducted a structured, qualitative, rapid reconnaissance survey of 180 actors from eight segments of the aquatic food value chain in three Nigerian states with contrasting geographies, Ebonyi, Kebbi, and Oyo. Results Results particularly important for future research and policy are as follows. (1) Partial vertical integration is a common feature of the organization of firms in all value chain segments, as a risk reduction strategy to overcome market imperfections and frictions. Scarcity and high cost of imported intermediate inputs is stimulating local innovation and import substitution manufacturing of feeds and fabricated items. (2) Inter-sectoral spillovers from the poultry industry have hastened the development of fish value chains, while improvements in power supply have enabled the expansion of cold storage capacity, facilitating the geographical lengthening of frozen fish value chains. (3) Rapid technological and/or institutional change is occurring in all value chain segments, including those usually viewed as traditional, such as processing and fishing. Logistics services are becoming more specialized and sophisticated, and digital communications technologies including social media play an increasingly important role in value chain coordination and marketing. (4) Increasing opportunity costs of time drive demand for convenience foods such as smoked and fried fish, which require little further preparation and can be stored at room temperature. Demand for farmed catfish is linked to growing consumption of food away from home at bars and restaurants. (5) Significant opportunities exist to improve the performance of value chains in terms of gender equity, environmental impacts, and food safety.